A companion to Locke - Stuart, Matthew (Blackwell companions to philosophy, 2015)
This collection of 28 original essays examines the diverse scope of John Lockes contributions as a celebrated philosopher, empiricist, and father of modern political theory. Explores the impact of Locke's thought and writing across a range of fields including epistemology, metaphysics, philosophy of science, political theory, education, religion, and economics; Delves into the most important Lockean topics, such as innate ideas, perception, natural kinds, free will, natural rights, religious toleration, and political liberalism; Identifies the political, philosophical, and religious contexts in which Locke's views developed, with perspectives from todays leading philosophers and scholars.